Experiments on Rapid Deposition of Sand from High-velocity Flows - Vrolijk, Peter; Southard, John (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1997)
Summary Observations of sand transport and rapidde position by strong sand-laden surges in an open channel, by means of high-speed motion pictures, revealed that the dominant effect is a process by which a laminar sheared layer, with sand concentrations approaching the threshold for immobilization by grain interlocking, develops as suspended sand becomes concentrated near the base of the flow. The laminar sheared layer climbs vertically with time as sediment is progressively immobilized at the base of the layer and added at the top from the overlying turbulent flow. The mobility of the laminar sheared layer is probably enhanced bycontinuous upward flow of interstitial water that is trapped within the layer asthe layer accumulates. As the flow weakens and the concentration of suspendeds and in the flow decreases, the laminar sheared layer thins and/or becomes immobilized, giving way to the familiar weak traction transport on a well-defined immobile sand bed. Particles reside in the laminar sheared layer only briefly, and move only a short distance before immobilization; the laminar sheared layers seem not to share essential features with traction carpets. Much of the coarser, structureles slower most parts of thick turbidites might have been emplaced by processes not unlike those described here. Our results suggest that the entire turbidity current need not be of extremely high density for an initial deposit to be formed rapidly from extremely high near-bed sediment concentrations.